INTERNET OF THING BASED CAR PARKING SYSTEM - Chouhan, Sunil; P, Sandhya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In the current era, we are facing a new problem of parking of vehicles. It is a major problem in urban cities. The problem is more tough because ofÂ continues growing number of vehicle and also size of vehicles. Car parking is not just a major problem in India but also in all over the world. We knowÂ that one million vehicles burn oil every day. In this paper, we propose an automatic and real-time system for automated car parking. This system would be implemented by the use of internet of things (IOTs). IOT refers as any physical thing that is connected to internet or exchanging information orÂ data between internet and physical device. Arduino Uno is a microcontroller used in IOT. It is used for building digital devices, and interactive objectsÂ that can sense and control physical devices. Our smart parking will be implementing using Arduino Uno board for car parking and Ethernet shield toÂ connect parking area with web or internet. By using our automated parking system, a user can save much time for searching free parking space. AnÂ infrared sensor has to be employed in each slot to check that a particular plot is vacant or not. Searching smart parking system helps people to searchÂ parking space accessible with the ease of IOT automation by supplying parking slot free information. The user can book in advance the parking slotÂ and update the information to the server. Every user has a unique id and password. In case a car in stolen and enter the parking IOT the server checksÂ the database and inform the police. Â